2012
DOI: 10.5851/kosfa.2012.32.4.428
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Nucleotide Compounds, and Chemical and Sensory Qualities of Duck Meat during Aging at 0℃

Abstract: The objective of this study was to identify appropriate aging conditions, changes in nucleotide-related compounds, chemical changes, and a sensory evaluation of duck meat during aging at 0 o C for 7 d. Twenty one 45-day-old Pekin white ducks samples were separated into breast and leg meat. ATP was not detected for almost the entire aging period because ATP was depleted immediately after slaughter. Inosine monophosphate (IMP) was highest on day 1 (26.69 µmol/g), and then it rapidly decreased to 7.11 µmol/g on d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…SPISLP [24] recommended that raw and packed meat with VBN content of 20 mg% is considered to be a threshold value to evaluate the degree of freshness. Kim et al [25] reported that many meat products do not decay, although their VBN content is 30 mg%. In this study, VBN contents…”
Section: Changes In Vbn Of Low-salt Frankfurters During Refrigerated mentioning
confidence: 99%
“…SPISLP [24] recommended that raw and packed meat with VBN content of 20 mg% is considered to be a threshold value to evaluate the degree of freshness. Kim et al [25] reported that many meat products do not decay, although their VBN content is 30 mg%. In this study, VBN contents…”
Section: Changes In Vbn Of Low-salt Frankfurters During Refrigerated mentioning
confidence: 99%
“…The adenosine triphosphate (ATP) degraded to AMP, IMP, inosine, hypoxanthine, and ribose after slaughtering and these compounds are related to meat flavor (Jayasena et al, 2013a;Kim et al, 2012c). IMP has a role as an umami taste enhancer and also It can be supportive evidence for the relationship between IMP contents and muscle composition since chicken breast meat is composed with 90% type IIB muscle fiber compared to thigh meat composed of type I muscle fiber (Jayasena et al, 2014) in accordance with Jaturasitha et al (2008).…”
Section: Nucleotide Contentsmentioning
confidence: 99%
“…SPISLP (2011) suggested that a VBN value of 20 mg% can be used as a threshold value to evaluate the degree of freshness of raw and packed meat. Kim et al (2012) reported that many meat products do not decay, though their VBN content is 30 mg%. In this study, VBN contents in seasoned pork did not exceed this range during the 20-d storage period ( p <0.05).…”
Section: Resultsmentioning
confidence: 99%